The perceived benefits and challenges of mobile network outsourcing in South Africa. - Baumann, Lixiang (My University, 2014)
Abstract Telecom operators today are seeking new ways to achieve greater efficiency and streamline their cost structures. Outsourcing has become one of the strategic means of optimising an organisation’s cost structure, improving performance, obtaining benefits through economics of scale, as well as gaining a faster time to market. Although outsourcing can be of great economic benefit, managing an outsourcing contract can be very challenging in the complex mobile network environment. This research aims to explore the perceived benefits gained and challenges faced by the South African Mobile Network Operators (“MNOs”) through outsourcing their network rollout, network Operations and Management (“O&M”) and network maintenance as a network-managed service to the infrastructure equipment vendors in the South African context. The research concludes with the following findings in terms of perceived benefits to be gained by the MNOs though network outsourcing: 1) The outsourcing option appears to be an unavoidable choice for most South African MNOs due to a lack of in-house skilled resources; 2) In the MNOs’ view, outsourcing is, in some cases, more expensive compared to in-sourcing or carrying out the activities in-house. The challenge of quantifying cost-saving remains a concern for MNOs when considering outsourcing network-managed services to vendors; 3) MNOs acknowledge that outsourcing enables them to benefit from the economics of scales through vendors’ vast technical skilled resources, latest technologies and products, as well as rich experience in network management. However, losing the core technical skilled resources remains a concerning factor leading to reluctance on the part of South African MNOs to conduct the outsourcing of large-scale network-managed services; 4) A high unemployment rate and complicated labour regulations put South African MNOs into a dilemma between wanting to obtain economic benefits through outsourcing versus losing local employment. This creates complications for MNOs, who are consistently seeking the means to create a viii lean organisational structure while simultaneously being under pressure from the government to prevent losing further employment in the country. In terms of challenges faced by the MNOs, the research finds the following: 1) The complex scope of work in telecom mobile network outsourcing contracts creates challenges in managing the outsource contracts. 2) Changing the mind-set of ‘letting go’ requires high commitment from operators. Changing the operators’ technology-centric work force into a contractor management-centric work force requires transformation within the operators. 3) Lengthy contract negotiation and complicated project implementation in the industry typically slows down progress and hence jeopardizes the achievement of business objectives when outsourcing. 4) Finally, there are numerous challenges in dealing with various vendors relating to the maturity of the vendors’ experience in managing a network-managed services contract.
MBA 2014
Keywords: Mobile communication systems,Telecommunication,Contracting out